Birds as status symbols in northern France: Boves Castle during the High Middle Ages, in its regional context. (20th July 2022) - Duval, Colin; Clavel, Benoît
Abstract: Boves Castle, located in northern France, was occupied between the 9th and 16th centuries AD. Under excavation since 1996, this high-status site has yielded more than six tons of faunal remains. Until now, archaeozoological studies have focused on the early occupation of the site (10th and 11th centuries AD), revealing specific supply and consumption strategies, widely based around birds. Aside from the very large amount of domestic fowl, Boves Castle is distinguished by the number and diversity of wild birds from various environments, including wetland, coastal, forested and anthropized areas. However, the special feature of this site is the importance of freshwater birds, especially large waders, which remained a status symbol until modern times in this region. On the basis of this outstanding example, and other high-status sites from the same region, we aim to discuss the importance and status of various domestic and game bird categories in northern France during the High Middle Ages. We will also address the subject of controlled hunting areas around castles and other high-status consumer sites, for a better understanding of the link between power and consumption during the medieval period.